Tıbbi müdahalelerde hekimin aydınlatma yükümlülüğü - (:unkn) unknown (My University, 2012)
Tıbbi müdahale, kişinin sağlığını koruma amacını taşısa da özünde vücut bütünlüğüne yöneliktir. Bu eylemi, hekim ile has- ta arasındaki ilişkiyi belirlemektedir. Aydınlatma, hekim için bir borç iken hasta için bir haktır. Hekimin her müdahalesi, hastanın aydınla- tılmış rızası alınmadığı takdirde hukuka aykırı olacağından hastanın aydınlatılması, tıbbî müdahalenin hukuka uygunluğunun temel şar- tıdır.

Medical intervention is intended to protect the health of people but for the physical integrity is based on an action. This is significant to determine legal relationship between physician and patient. Obligation to inform is an obligation of physician also a right of patient. So that medical lawfull attention based on patient’s informed consent, physicians each attention is unlawfull without giving informed consent and fullfill the obligation to inform the patient.
The oblıgatıon of ınformıng the physıcıan of medıcal ınterventıon
Keywords: Tıbbi Etik